Mitochondria and ageing in model systems - Trifunovic, Aleksandra (Henry Stewart Talks, 2018)
Mitochondria function/dysfunction and related outcomes, Metabolic rate theory of aging, Beneficial effects of caloric restriction, ROS production and oxidative stress effect on aging, Free radical theory of aging, Mitochondrial DNA mutations phenotypes